Using Cosmogenic 10Be Exposure Dating and Lichenometry to Constrain Holocene Glaciation in the Central Brooks Range, Alaska. Issue 1 (1st February 2017) - Pendleton, Simon L.; Briner, Jason P.; Kaufman, Darrell S.; Zimmerman, Susan R.
ABSTRACT: We compile new and previously published lichenometric and cosmogenic 10 Be moraine ages to summarize the timing of Holocene glacier expansions in the Brooks Range, Arctic Alaska. Foundational lichenometric studies suggested that glaciers likely grew to their Holocene maxima as early as the middle Holocene, followed by several episodes of moraine building prior to, and throughout, the last millennium. Previously published 10 Be ages on Holocene moraine boulders from the north-central Brooks Range constrain the culmination of maximum Holocene glacier advances between 4.6 ka and 2.6 ka. New 10 Be ages of moraine boulders from two different valleys in the central Brooks Range published here show that maximum Holocene glacial extents in these valleys were reached by 3.5 ka and ca. 2.6 ka, supporting previous studies showing that Holocene maximum, or near-maximum, glacial extents in the Brooks Range occurred prior to the Little Ice Age. However, in-depth reconciliations between glacier extent and local and regional climate are hampered by uncertainties associated with both lichenometry and 10 Be dating.